ANTIMICROBIAL ACTIVITY OF ANISOCHILUS CARNOSUS (L.F.) WALL AGAINST THE HUMAN GASTRIC PATHOGEN HELICOBACTER PYLORI - Shetty, Vignesh; Lobo, Richard; Kumar, Nimmy; Lingadakai, Ramachandra; C Pai, Ganesh; Balaraju, Girish; Ballal, Mamatha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The prevalence of Helicobacter pylori in India is high, and majority leads to severe gastrointestinal infections. Existing treatment regimens for H. pylori infections have increased failure rates and adverse side effects that desire the search for an effective substitute therapy. Anisochilus carnosus (L.f.) wall (Lamiaceae), a herb which grows once in a year at high elevation is used widely in traditional treatment for the complaints of gastric ulcer and skin diseases. The present study was performed to assess the antibacterial activity of A. carnosus (L.f.) wall, against clinical isolates of H. pylori in vitro. Methods: A. carnosus leaves were collected-dried and extracted with water and ethanol by cold maceration with ethanol by soxhlet method. The minimum inhibitory concentration (MIC) of extracts was made and tested against 32 clinical and 1 reference strains of H. pylori. Results: A. carnosus (L.f.) wall inhibited the growth of most of the clinical H. pylori strains. The MIC of A. carnosus (L.f.) wall extracted by cold maceration (aqueous and ethanol) and Soxhlet apparatus (ethanol) ranged from 500 to 62.5 Î¼g/ml, and the majority of the clinical H. pylori strains were inhibited at the MIC of 500 Î¼g/ml of aqueous, ethanol, and Soxhlet ethanol extraction were 63.63%, 43.75%, and 71.87%, respectively. Conclusion: A. carnosus (L.f.) wall is an efficient inhibitor of H. pylori growth in vitro. A. carnosus (L.f.) wall revealed enormous therapeutic potential to H. pylori infection as it was extremely active in the suppression of H. pylori. Hence, it can be taken as a potential agent against several H. pylori linked gastric pathogenic progressions.